Optimal timing of tau pathology imaging and automatic extraction of a reference region using dynamic [18F]THK5317 PET - Jonasson, My; Wall, Anders; Chiotis, Konstantinos; Leuzy, Antoine; Eriksson, Jonas; Antoni, Gunnar; Nordberg, Agneta; Lubberink, Mark (NeuroImage clinical, 2019)
[18F]THK5317 is a PET tracer for in-vivo imaging of tau associated with Alzheimer's disease (AD). This work aimed to evaluate optimal timing for standardized uptake value ratio (SUVR) measures with [18F]THK5317 and automated generation of SUVR-1 and relative cerebral blood flow (R1) parametric images. Nine AD patients and nine controls underwent 90 min [18F]THK5317 scans. SUVR-1 was calculated at transient equilibrium (TE) and for seven different 20 min intervals and compared with distribution volume ratio (DVR; reference Logan). Cerebellar grey matter (MRI) was used as reference region. A supervised cluster analysis (SVCA) method was implemented to automatically generate a reference region, directly from the dynamic PET volume without the need of a structural MRI scan, for computation of SUVR-1 and R1 images for a scan duration matching the optimal timing. TE was reached first in putamen, frontal- and parietal cortex at 22 ± 4 min for AD patients and in putamen at 20 ± 0 min in controls. Over all regions and subjects, SUVR20–40-1 correlated best with DVR-1, R2 = 0.97. High correlation was found between values generated using MRI- and SVCA-based reference (R2 = 0.93 for SUVR20–40-1; R2 = 0.94 for R1). SUVR20–40 allows for accurate semi-quantitative assessment of tau pathology and SVCA may be used to obtain a reference region for calculation of both SUVR-1 and R1 with 40 min scan duration. •This study evaluates optimal timing for SUVR-1 estimation of tau binding with [18F]THK5317 PET.•A time interval of 20–40 min was optimal for SUVR-1 estimates of [18F]THK5317 PET.•Later scanning times induced spatially-varying biases in binding estimates.•A clustering method can be used to extract a reference time activity curve from dynamic [18F]THK5317 PET data.•The clustering extracted reference TAC was used as input for generation of parametric images of SUVR-1 and R1.